MANFAAT PENDIDIKAN DASAR BAGI ANGGOTA KOPERASI SIMPAN PINJAM CREDIT UNION PANCUR KASIH TEMPAT PELAYANAN BENGKAYANG - MARTONO MARTONO (STIE 'INDONESIA' Pontianak, 2020)
There are five pillars of credit cooperatives, namely Education, Self-help, Solidarity, Innovation and Unity. Basically Credit Union was born from the stage of education, developed through education and dependent on education. For this reason, every prospective member (community) who will join the Credit Union is required to attend education, because the educational aspect within the scope of the development of savings and loan cooperatives is very important. Plus the main goal of basic education is to recognize and deepen the ins and outs of Credit Union, the unification of vision and mission as a n Credit Union Workshop Services. The method in this research is descriptive analysimember of Credit Union, changes in physical, mental, emotional, and spiritual aspects of life principles and paradigms, understanding history, financial intelligence, management regulations on AD / ART, and as a condition to become a member. Basic education for Credit Union members is an obligation for cooperatives as mentioned in the cooperative principle in Act Number 25 of 1992 Article 5 paragraph 2a. This study aims to determine the benefits of basic education for members of the Pancur Kasih Credit Unios method. This is ex post facto research. The population in this study was 8,000 members. The number of samples in this study were 80 members. Data collection techniques in this study are direct communication techniques (interview guidelines), indirect communication techniques (questionnaires), and documentary techniques (members' bad credit data). The results of this study indicate that there is a positive influence on the basic training of members of the responsibilities and obligations of members in the KSP CU Kasih Bengkayang TP. This can be seen from the t value of 5.632 which shows that there is an effect of the basic training of members on the responsibilities and the results of members' obligations. When compared with t table at the 0.05 significance level of 1.992, so Ha is accepted. The conclusion of this study is the basic training of members has a significant effect on the responsibilities and obligations of members in the KSP CU Kasih Bengkayang TPU